PreHevbrio: the first approved 3-antigen hepatitis B vaccine - Timo Vesikari; Joanne M Langley; Vlad Popovic; Francisco Diaz-Mitoma (Taylor & Francis Group, 2023)
Introduction Hepatitis B remains a major cause of death and morbidity worldwide. Universal childhood immunization programs have been very successful, but many adults remain unprotected or are not optimally protected. PreHevbrio [Hepatitis B Vaccine (recombinant)]is a highly immunogenic 3-antigen (S/pre-S1/pre-S2) hepatitis B vaccine (3A-HBV) that recently received marketing authorization in the United States (2021), the European Union, United Kingdom (2022 - brand name PreHevbri), and Canada (2022- brand name PreHevbrio) for the prevention of infection caused by all known subtypes of the hepatitis B virus and the delta virus in adults 18 years and older. Areas covered This review details the development of 3A-HBV and summarizes the results of the phase 3 clinical trials that support its immunogenicity and safety in adults. Expert Opinion 3A-HBV is highly immunogenic in adults of all ages, including older adults and subgroups that respond sub-optimally to conventional single S-antigen hepatitis B vaccines (1A-HBV), such as those with obesity, type 2 diabetes, and smokers. 3A-HBV provides higher seroprotection rates after each vaccination compared to conventional 1A-HBV vaccines, allowing for more rapid protection. The higher overall immunogenicity is also reflected in more durable seroprotection years after vaccination, as supported by a follow-up study to one of the phase 3 studies.